Urethral caruncle: a diagnosis conundrum in teenage girl: a case report - Dasrilsyah, Rima Anggrena; Kamarudin, Maherah; Apana, Aruku Naidu (Royal Thai College of Obstetricians and Gynaecologists, 2024)
Urethral caruncle in young female is uncommon. Here we report a case of it seen in our urogynaecology outpatient clinic which was surgically managed. An 18-year-old teenage girl presented with periurethral mass for few months. Suspicion of the diagnosis of urethral caruncle was made clinically and we proceeded with surgical excision of the mass under local anaesthesia. Histopathological examination confirms the diagnosis. This case shows that although the presentation was atypical and is rarely seen in teenagers, it should be considered as one of the differentials when dealing with vaginal mass besides urethral prolapse, urethral diverticulum, urethrocele or even malignancy. Although urethral caruncle is more commonly associated with postmenopausal due to the hypoestrogenic state, it is important to integrate a clinical suspicion and decision for excision based on presenting symptoms.